Publishing a writer's memoir - Godwin, Gail (Bloomsbury, 2016)
"Publishing is a personal story of a writer's hunger to be published, the pursuit of that goal, and then the long haul--for Gail Godwin, forty-five years of being a published writer and all that goes with it. A student at the University of North Carolina at Chapel Hill in 1958, Godwin met with Knopf scouts who came to campus every spring in search of new talent. Though her five pages of Windy Peaks were turned down and the novel never completed, she would go on to publish two story collections and fourteen novels, three of which were National Book Award finalists, five of which were New York Times bestsellers. Publishing reflects on the influence of her mother's writing hopes and accomplishments, and recalls Godwin's experiences with teachers Kurt Vonnegut and Robert Coover at the Iowa Writers' Workshop; with John Hawkins, her literary agent for five decades; with John Irving and other luminaries; and with her editors and publishers. Recollecting her long and storied career, Godwin maps the publishing industry over the last fifty years, a time of great upheaval and ingenuity. Her eloquent memoir is illuminated by Frances Halsband's evocative black-and-white line drawings throughout. There have been memoirs about writing and memoirs about being an editor, but there is no other book quite like Publishing for aspiring writers and book lovers everywhere"--Provided by publisher.